2012
DOI: 10.1002/adma.201203426
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Silica Films on Metals: The Long and Winding Road to Understanding the Atomic Structure

Abstract: This paper critically reviews the experimental and theoretical studies on the growth of ultrathin silica films onto metal single crystal substrates reported to date. The silica films on Mo(112) and Ru(0001) are discussed in more detail to demonstrate the key roles of the multi-technique approach and interplay between experiment and theory in the quest for understanding the atomic structure of the films. The results show the structural complexity and diversity of silica overlayers on metals, providing further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
127
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(140 citation statements)
references
References 102 publications
11
127
0
2
Order By: Relevance
“…In addition, this film was prepared using isotopically labelled molecular oxygen, 18 O 2 . As expected, a new broad band centered at 1190 cm -1 is observed in IRA-spectrum which is characteristic for three-dimensional, bulk-like ( 18 O-labeled) silica [1,7,9] (see Fig. S2), suggesting that this sample contains also some silica nanoparticles.…”
Section: Pure Silicate Filmsmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition, this film was prepared using isotopically labelled molecular oxygen, 18 O 2 . As expected, a new broad band centered at 1190 cm -1 is observed in IRA-spectrum which is characteristic for three-dimensional, bulk-like ( 18 O-labeled) silica [1,7,9] (see Fig. S2), suggesting that this sample contains also some silica nanoparticles.…”
Section: Pure Silicate Filmsmentioning
confidence: 62%
“…Silicate and aluminosilicate thin films grown on metal substrates have recently received considerable attention as well-defined models for studying surface chemistry of silica-based materials, in particular of zeolites, as well as crystal-glass transitions exemplified by silica [1][2][3][4]. It is well established that the thinnest silica film forms a hexagonal layer of corner-sharing [SiO 4 ] tetrahedra (referred to as "silicatene" in analogy to graphene [5]) which is strongly bound to a metal support through Si-O-Metal linkages [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mo(110), Mo(112) and Ru(0001) have all been shown to be ideal candidates for the growth of these films and their structural properties have been well documented. [6][7][8][9][10][11][12][13][14][15][16][17] From these studies it has been shown that the type of silica film can be solely determined by its infrared vibration band: ∼1300 cm −1 for a bilayer, ∼1250 cm −1 for a thick, vitreous film, and ∼1065 or ∼1135 cm −1 for a monolayer film on Mo(112) or Ru(0001), respectively. 16 SiO 2 films have also been successfully grown on Ni(111) 18 , Pd(100) 19 , and Pd(111) 20 , but have not been characterized to the extent of the aforementioned surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…9,16 The trend observed for the structure of these thin films was shown to follow two parameters: lattice mismatch and oxygen affinity of the metal support. A greater lattice mismatch results in a non-crystalline thin film, as was shown for the bilayer on Pt(111) compared to Ru(0001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation